2022
DOI: 10.1002/ijop.12836
|View full text |Cite
|
Sign up to set email alerts
|

Authoritarianism and perceived threat from the novel coronavirus

Abstract: The threat of COVID‐19 has triggered nationalism, prejudice and support for anti‐democratic political systems around the world. Authoritarianism—an individual's orientation toward social conformity and individual autonomy—shapes interpretations of and responses to threat. We drew on theories of authoritarianism and threat to propose that authoritarians and libertarians will interpret the threat of COVID‐19 in distinct ways. An online survey of 368 Scottish nationals was administered via the Prolific platform. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…A second limitation in understanding the link between authoritarianism and anti-mitigation efforts is the lack of data that measure both realistic and symbolic threats along with beliefs and about mitigation efforts. Deason and Dunn (2022) show that authoritarians viewed symbolic threats such as mitigation efforts as more threatening than the health threats from COVID-19 providing evidence for our assumed mechanism that links authoritarianism and mitigation behaviors. And the relationship between authoritarianism and mitigation behaviors we find across data sets is consistent with such a finding although we cannot rule out alternative casual linkages.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…A second limitation in understanding the link between authoritarianism and anti-mitigation efforts is the lack of data that measure both realistic and symbolic threats along with beliefs and about mitigation efforts. Deason and Dunn (2022) show that authoritarians viewed symbolic threats such as mitigation efforts as more threatening than the health threats from COVID-19 providing evidence for our assumed mechanism that links authoritarianism and mitigation behaviors. And the relationship between authoritarianism and mitigation behaviors we find across data sets is consistent with such a finding although we cannot rule out alternative casual linkages.…”
Section: Discussionmentioning
confidence: 68%
“…Disaggregating the nature of the threats posed by the pandemic provides additional theoretical insights into how different groups—including authoritarians—responded to it. While the material costs of restrictions (as physical consequences of infection) represent “realistic” threats, the social disruption they cause and their threat to group cohesion represent “symbolic” threats (Deason and Dunn, 2022; Kachanoff et al, 2021). Due to its direct negative impact on physical health, the SARS-CoV-2 pathogens represented a realistic threat.…”
Section: Rethinking Pandemic Threats and Authoritarian Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, an interplay of policy making, political processes and subjective threat perception is quite conceivable ( cf. Deason and Dunn, 2022 ) or that threat may only moderate the effects of authoritarianism on other constructs like outgroup rejection ( Hartman et al, 2021 ) Cross-cultural and international comparisons as well as longitudinal studies could help shed light on this dynamic to understand how politics can promote solidarity in times of crises instead of fostering an authoritarian dynamic.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Golec de Zavala et al (2020) reported an increase in authoritarianism and related attitudes in Poland using latent growth curve modeling on a representative, longitudinal data set. Moreover, Hartman et al, 2021 could show that anxieties about the pandemic increased the effect of authoritarianism on anti-immigrant attitudes in the United Kingdom and Ireland, and Deason and Dunn (2022) demonstrated that authoritarians were more likely to interpret the COVID-19 pandemic as a symbolic threat to their prevailing values than libertarians did.…”
Section: Introductionmentioning
confidence: 99%